2021
DOI: 10.3390/jof7050372
|View full text |Cite
|
Sign up to set email alerts
|

Rhizopus oryzae-Mediated Green Synthesis of Magnesium Oxide Nanoparticles (MgO-NPs): A Promising Tool for Antimicrobial, Mosquitocidal Action, and Tanning Effluent Treatment

Abstract: The metabolites of the fungal strain Rhizopus oryaze were used as a biocatalyst for the green-synthesis of magnesium oxide nanoparticles (MgO-NPs). The production methodology was optimized to attain the maximum productivity as follows: 4 mM of precursor, at pH 8, incubation temperature of 35 °C, and reaction time of 36 h between metabolites and precursor. The as-formed MgO-NPs were characterized by UV-Vis spectroscopy, TEM, SEM-EDX, XRD, DLS, FT-IR, and XPS analyses. These analytical techniques proved to gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(46 citation statements)
references
References 113 publications
4
27
0
1
Order By: Relevance
“…Data represented in Table 2 reported that the activity of Se-NPs against different instar larvae was dose and time-dependent. This result is compatible with others who reported that the toxicity of biosynthesized CuO-NPs, MgO-NPs, and Ag-NPs was dose-dependent [68][69][70]. Data analysis showed that the highest mortality percentages were achieved at the highest Se-NPs concentration (25 ppm), which were 34.3 ± 0.3%, 32.3 ± 0.3%, 46.0 ± 1.0%, 35.7 ± 0.6%, and 39.3 ± 0.3% for 1st to 5th instar larvae after 24 h. These mortality percentages were increased by increasing incubation time to reach 89.7 ± 0.3%, 78.3 ± 0.3%, 72.3 ± 0.6%, 63.7 ± 0.3%, and 68.7 ± 0.3% for the same instar larvae after 72 h (Table 1).…”
Section: Larvicidal Activitysupporting
confidence: 93%
“…Data represented in Table 2 reported that the activity of Se-NPs against different instar larvae was dose and time-dependent. This result is compatible with others who reported that the toxicity of biosynthesized CuO-NPs, MgO-NPs, and Ag-NPs was dose-dependent [68][69][70]. Data analysis showed that the highest mortality percentages were achieved at the highest Se-NPs concentration (25 ppm), which were 34.3 ± 0.3%, 32.3 ± 0.3%, 46.0 ± 1.0%, 35.7 ± 0.6%, and 39.3 ± 0.3% for 1st to 5th instar larvae after 24 h. These mortality percentages were increased by increasing incubation time to reach 89.7 ± 0.3%, 78.3 ± 0.3%, 72.3 ± 0.6%, 63.7 ± 0.3%, and 68.7 ± 0.3% for the same instar larvae after 72 h (Table 1).…”
Section: Larvicidal Activitysupporting
confidence: 93%
“…The biotechnological processes depending on biological entities are usually correlated with the environmental conditions which may have positive or negative impacts [30,31]. Therefore, the effects of the environmental parameters on biodegradation of cypermethrin using Lysinibacillus cresolivuorans strain HIS7 were investigated.…”
Section: Optimizing Factors Affecting the Biodegradation Processmentioning
confidence: 99%
“…The plates were preserved in fridge for one hour before incubation for 24h (bacteria and unicellular fungi) at 35±2°C or 48h (multicellular fungi) at 28± 2°C. At the end of incubation period, the diameter of clear zone around each well was recorded by mm (Hassan et al, 2021). The experiment was achieved in triplicate.…”
Section: Rooting Stagementioning
confidence: 99%